Religious Pluralism According to Farid Esack: A Hermeneutic Study of Wilhelm Dilthey: Pluralisme Agama Menurut Farid Esack: Sebuah Kajian Hermeneutik Wilhelm Dilthey - Farah, Naila; Mafrikhana, Fina (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2025)
This study explores Farid Esack's perspective on religious pluralism through the lens of Wilhelm Dilthey's hermeneutic theory, which emphasizes lived experience (Erlebnis), expression (Ausdruck), and understanding (Verstehen). Esack, a South African Muslim scholar and activist, developed his pluralistic thought in response to experiences of systemic injustice under apartheid and exposure to interfaith dynamics during his education in Pakistan. This research aims to analyze how Esack's personal experiences shaped his theological approach to pluralism and to articulate how his liberative hermeneutics of the Qur'an fosters interfaith solidarity and justice. Employing a qualitative, hermeneutic approach, the study interprets Esack's key writings in conjunction with his biographical context. The findings reveal that Esack's conception of pluralism transcends tolerance, emphasizing active recognition and cooperation across religious boundaries as a moral imperative rooted in Islamic teachings. His praxis-based hermeneutics advocate for justice, dignity, and liberation, particularly for the oppressed, offering a transformative model of interfaith engagement. This study contributes to contemporary Islamic discourse on pluralism, justice, and coexistence.